2003
DOI: 10.1637/0005-2086(2003)047[0163:lpoalp]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Low Persistence of a Large-Plasmid-Cured Variant of Salmonella enteritidis in Ceca of Chicks

Abstract: In order to estimate the contribution of Salmonella in the persistence of this bacterium in chicks, we compared the persistence of a Salmonella enteritidis strain and its plasmid-cured variant in a chicken asymptomatic carrier state model. After oral inoculation, colonization with the plasmid-cured strain was significantly reduced (P < 0.001) in the ceca of chicks from the third week postinoculation and persisted for a shorter period than the wild-type strain. Moreover, numbers of S. enteriditis-infected liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…C); then Salmonella was not detected in spleen 3 to 4 weeks postinfection (pi) even though a few bacteria could still be detected in this organ from weeks 4 to 6 pi in a few animals as previously described (Berthelot‐Hérault et al ., ). This has been also described for liver (Virlogeux‐Payant et al ., ). In contrast to the short‐term infection of the spleens, S .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…C); then Salmonella was not detected in spleen 3 to 4 weeks postinfection (pi) even though a few bacteria could still be detected in this organ from weeks 4 to 6 pi in a few animals as previously described (Berthelot‐Hérault et al ., ). This has been also described for liver (Virlogeux‐Payant et al ., ). In contrast to the short‐term infection of the spleens, S .…”
Section: Resultsmentioning
confidence: 97%
“…However, the mouse models do not seem to be representative of the carrier state observed in chicken and pigs where no persistent systemic infection occurs. In these farm animals, systemic infection precedes persistence in caeca and disappears from spleen and liver, a few weeks after infection (Virlogeux-Payant et al, 2003). A previous study has shown that an intravenous inoculation of Salmonella can lead to caecal persistence (Girard Santosuosso et al, 1998), it is, therefore, important to determine whether systemic infection is required to induce Salmonella carrier state in caeca and/or it determines the development of the carrier state.…”
Section: Resultsmentioning
confidence: 99%
“…the spleen, liver and gall bladder; figure 1 ). The vessels were chosen because Salmonella is able to spread through the body via the blood, and the spleen and liver as they are colonized by Salmonella in chicks [ 37 , 38 ]. Finally, we decided to study the gall bladder as well because Gonzalez-Excobedo & Gunn [ 39 ] demonstrated that the gallbladder epithelium contributed to establishing and maintaining chronic carriage in mice.…”
Section: Resultsmentioning
confidence: 99%
“…Heidelberg in layer chickens [ 44 ], or for a large-plasmid-cured variant of S . Enteritidis [ 46 ]. In the present study, it can be suspected that multiplication of the pESI– strain in the caeca was less effective which resulted in a lower excretion rate of positive birds being under the detection limit of direct plating.…”
Section: Discussionmentioning
confidence: 99%
“…As these features were identical in the actual study the shedding patterns can clearly be attributed to the different nature of the used S. Infantis strains. An explanation for this might be the fact that different clones of one Salmonella species are able to adapt differently to the chicken intestine as shown for S. Heidelberg in layer chickens (46), or for a large-plasmid-cured variant of S. Enteritidis (48). In the present study it can be suspected that multiplication of the pESI-strain in the caeca was less effective which resulted in a lower excretion rate of positive birds being under the detection limit of direct plating.…”
Section: Discussionmentioning
confidence: 99%